A Cohort Study: Urine Interferon Gamma-Induced Protein 10 As A Non-Sputum Biomarker in Diagnostic and Treatment Monitoring in Patients with Active Pulmonary Tuberculosis - Subroto, Hendra; Parwati, Ida; Alisjahbana, Bachti; Rita, Coriejati; Indah Efriyani, Yuhpita; Natasya Moses, Joycelynn (Journal of Neonatal Surgery, 2025)
There are still limitations in the diagnosis of tuberculosis (TB), and developing monitoring tools to predict treatment outcomes for TB patients is important. Sputum collection is not only challenging but also has low sensitivity when used as a diagnostic specimen. Interferon gamma-inducible protein 10 (IP-10) is a potential biomarker of diagnosis and treatment response in tuberculosis. In this study, we measured IP-10 levels in urine samples taken at diagnosis, following the intensive treatment period, and post-treatment from patients with active tuberculosis. This was a comparative observational cohort study on new active pulmonary TB patients who were >18 years old at the TB Clinic of Dr. Hasan Sadikin General Hospital Bandung. IP-10 was measured using enzyme-linked immunosorbent assays in urine samples collected from 39 patients with active TB (26 patients with drug-resistant and 13 patients with drug-sensitive tuberculosis) and 34 healthy adults (73 total individuals). Thirty-nine patients who met the inclusion criteria were followed up until completion of TB treatment. There was a decrease in urine ip-10 levels in both the DR-TB vs DS-TB groups at diagnosis, after the intensive phase, and after treatment. (16.1 vs 13.3 pg/mL; 11.7 vs 8.4 pg/mL; 3.6 vs 3.2 pg/mL). IP-10 in urine has good accuracy with an AUC value of 0.847 in detecting Active TB with a cutoff value of 8.3 pg/mL, sensitivity of 97.4%, specificity of 61.8%, PPV 74.5%, NPV 95.5%, LR+ 2.55, and LR- 0.04. Urine IP-10 levels in active pulmonary TB patients decreased significantly after intensive phase and at the end of treatment (p<0.001), and urine IP-10 levels have the potential as a non-sputum-based marker for treatment-related TB monitoring.